1994
DOI: 10.1152/jappl.1994.77.3.1309
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of pulmonary atrial natriuretic peptide receptors in rats exposed to chronic hypoxia

Abstract: We hypothesized that a downregulation in pulmonary atrial natriuretic peptide (ANP) receptors helps raise plasma ANP levels during chronic hypoxia. We measured in vivo pulmonary uptake and plasma clearance of 125I-ANP and in vitro pulmonary binding kinetics of 125I-ANP in normoxic and chronically hypoxic rats. Exposure to 21 days of hypobaric (0.5 atm) hypoxia did not decrease specific binding of 125I-ANP in the kidney, but pulmonary binding decreased 35 and 75% after 1 and 3 days of hypoxia, respectively, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Several other mechanisms have been proposed. Hypoxia has been shown to increase cardiac gene expression of BNP [23,24] and decrease lung expression of the NPR-C clearance receptor leading to increased plasma levels of BNP in animal models [25]. Transcription of the BNP gene has been described not only in cardiac myocytes but also in the lung [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several other mechanisms have been proposed. Hypoxia has been shown to increase cardiac gene expression of BNP [23,24] and decrease lung expression of the NPR-C clearance receptor leading to increased plasma levels of BNP in animal models [25]. Transcription of the BNP gene has been described not only in cardiac myocytes but also in the lung [26].…”
Section: Discussionmentioning
confidence: 99%
“…In humans and animals, exposure to chronic hypoxia results in a sustained elevation in circulating ANP levels due to both an increase in ANP synthesis in the right heart and a decrease in pulmonary ANP clearance (Klinger et al, 1996). Studies have shown that ANP is a selective vasorelaxant of the pulmonary vessels and counteracts the pathogenic mechanisms involved in PH (Adnot et al, 1987(Adnot et al, , 1988Jin et al, 1990;Raffestin et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, right heart dysfunction due to severe lung disease from a variety of etiologies can cause elevated NP levels. The mechanism is likely due to release of peptide from the right ventricular myocardium (28), although decreased lung expression of the NPR-C clearance receptor in response to hypoxia has been demonstrated in animal models (29). This scenario can be seen in severe chronic obstructive pulmonary disease, primary pulmonary hypertension, and other causes of pulmonary hypertension (28,30,31).…”
Section: Pulmonary Diseasementioning
confidence: 99%